Measurement Modifications for Assessing Organizational Climate in Hospitals - Wallace, Marc J.; Ivancevich, John M.; Lyon, Herbert L. (Academy of Management Journal, 1975)
The degree to which the Halpin and Croft Organizational Climate Description Questionnaire generalizes from business and educational settings to hospital settings was investigated. Two criteria were established for the instrument: (a) reliability, and (b) factor structure replication from previously investigated settings to hospital settings. The results were cross-validated in two hospitals.